Intranasal infection and contact transmission of Zika virus in guinea pigs - Yong-Qiang Deng (Nature Portfolio, 2017)
Human case studies suggest that Zika virus can be transmitted independently of mosquitoes and sexual contact. Here, the authors show intranasal Zika infection in different animal models and show that contact transmission of Zika virus occurs in guinea pigs.